PEMBUATAN BUBUR INSTAN DENGAN PENAMBAHAN KONSENTRAT PROTEIN IKAN KEMBUNG (Rastrelliger sp) - Manoppo, Madeline G.; Rieuwpassa, Fredrik; Wenno, Max R.; Sormin, Raja B. D.; Kaya, Adrianus O. W.; Wattimena, Martha L.; Nanlohy, Esterlina E. E. M. (Pattimura University, 2025)
Mackerel is a seawater fish that is widely found in Indonesian waters. Mackerel has a fairly high nutritional value which is an important economic fish and this fish has a fairly good and savory taste so it is widely loved by the public. Analog rice is rice made from non-rice raw materials, has a shape similar to rice rice and has excess nutritional content that can be designed according to consumer wishes. Analog rice can be used for making instant porridge practically. To increase the nutritional value of instant porridge, it will be added with mackerel protein concentrate. Protein concentrate is very good if added to porridge dishes that are suitable for consumption by babies and adults. The purpose of this study is to find out the organoleptic value and proximate content in instant porridge with the addition of mackerel protein concentrate. The method in this study is an experimental or experimental method. Finished data The research was processed descriptively in the form of graphs and images with organoleptic test parameters and proximate test. The results of this study are that in the organoleptic test there are 4 treatments where the panelists prefer the A1 treatment with a color value of 8,0; taste 6,0; aroma 4,0; texture 8,0 so that it can be taken as the best value to test its chemical parameters. The results of the proximate test in the selected treatment averaged 80.32% water content, 0.17% ash content, 3.25% protein content, 1.71% fat content and 16.31% carbohydrates. . Key words: Mackerel Fish, Analog Rice, Instant Porridge, Fish Protein Concentrate, Nutritional content